Perspektif Hukum Islam Terhadap Biaya Administrasi Transfer Dana melalui BSI Mobile - Wahyuda, Agung Taufik; Batubara, Enika; Dhar, Ali Ad; Rodiah, Rindur; Chasnun, Faiz Nayla (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The emergence of Islamic banks in Indonesia at the end of the 19th century until they developed more than 20 years to date has made us understand the importance of the existence of an Islamic economy in Indonesia. This research uses library research or library research, namely research conducted by collecting data or scientific writing that is intended to be the object of research, library data collection, or studies conducted to solve a problem. problems which are mostly based on a critical and thorough analysis of relevant literature. Based on muamalah fiqh analysis, interbank fund transfer transactions through the BSI Mobile application are permitted because the transactions carried out avoid usury, maisir, gharar, tadlis transactions and there are benefits to ease fund transfer transactions between different banks. In addition, the contract used is also in accordance with DSN MUI Fatwa No. 10/DSN-MUI/IV/2000 concerning Wakalah and DSN MUI Fatwa No. 113/DSN-MUI/IX/2017 concerning Wakalah bi al-Ujrah. Keywords: Islamic law, administration, BSI Mobile